(untitled) (XXI Century. Spanish Literature and Culture, 2009)
With this article Antonio Colinas vindicates the figure of one of our most forgotten contemporary poets, Pablo García Baena, cofounder of the journal Cántico. Through an essential analysis of his literary work, Colinas highlights the following topics as key in understanding the Cordobés writer: the naturalness; the telluric force of his poetry; the meaning of space, and particularly of his native city in the configuration of his poetic world, in the creation of his cities (Córdoba, Venetia, Delfos, tec.)—symbols to which he does not return not because of mere aesthetic conventionalism, but rather out of a sense of pure vitalism; and, finally, the experience of the sacred, showing the will of human beings to transcend, to reach the fullness of being, universality.